Determination of soil erodibility, K factor for Sungai Kurau soil series / Rozaini Ramli and Intan Shafika Saiful Bahri - Ramli, Rozaini; Saiful Bahri, Intan Shafika (Universiti Teknologi MARA Pulau Pinang, 2011)
Many insidents of landslides and erosion have occured in Malaysia lately, especially in the higlands areas, properties were damaged and lives were lost.